2022
DOI: 10.1002/ijfe.2700
|View full text |Cite
|
Sign up to set email alerts
|

Competition, stability, and institutional environment: The case of dual banking economies

Abstract: We measure the impact of competition and institutional quality on stability for dual banking economies. Our sample comprises 492 banks (109 Islamic and 383 conventional banks) from 17 countries with dual‐banking systems. The sample period is from 2005 to 2020. The estimations are performed using Two Step System Generalized Method of Moments approach. Our findings reveal heterogeneous effect of competition on stability. We found the evidence of competition‐stability paradigm in case of full sample as well as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Furthermore, a strong institutional framework can also increase the efficiency of the financial system by reducing systemic risk and promoting the safety and stability of the financial sector. Financial stability results in greater efficiency as resources are saved from being used to manage systemic risks [ 22 ], Azmi, Anwer [ 54 ]. Overall, findings of current study significantly contribute to the existing literature by highlighting the importance of strong institutional framework in enhancing financial system efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a strong institutional framework can also increase the efficiency of the financial system by reducing systemic risk and promoting the safety and stability of the financial sector. Financial stability results in greater efficiency as resources are saved from being used to manage systemic risks [ 22 ], Azmi, Anwer [ 54 ]. Overall, findings of current study significantly contribute to the existing literature by highlighting the importance of strong institutional framework in enhancing financial system efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Financial stability results in greater efficiency as resources are saved from being used to manage systemic risks. Azmi, Anwer [ 54 ] found that better quality of economic and political institutions leads to greater bank stability, by reducing information asymmetry and adverse selection. Most of the indicators of institutional quality are found to play an important role in enhancing banking sector efficiency [ 22 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%